Fulfillment Of Water Needs With Rainwater Harvesting Concept at Campus Universitas Padjadjaran, Jatinangor, West Java - SUGANDA, BOMBOM RACHMAT; Barkah, Mochamad Nursiyam; Iskandarsyah, Teuku Yan Waliyana Muda; Natasia, Nanda; Dwi Hadian, Mohamad Sapari (Journal of Geological Sciences and Applied Geology, 2017)
University of Padjadjaran (Unpad) as a means of education and research has need of water large quantity. Until now meeting the needs of water was carried out as a conventional namely the usage of groundwater. Through the passing of time, the constant use of groundwater and land use change in the catchment area may pose a risk of ground water crisis. Rainwater in the university environment has large potential with an average annual rainfall is 961.92 mm. The concept of rainwater harvesting by using potential water which be runoff will become the source of water to the fulfillment of a need. Unfortunately, rainwater that become runoff can contain bacteria and chemical contents that may be harmful to health. It is necessary for the screening process using filtration and membrane technology that can clean water and produce safe water to drink.